(untitled) (Global Journal of Human-Social Science, 2026)
This study investigates the syntactic phenomenon of topicalisation in Tupuri. Specifically, it examines the fronting of subjects, objects, and adjuncts to the left periphery of the clause within a cartographic framework, assessing how Tupuri aligns with cross-linguistic patterns of topicalisation. Data were collected through a one-month field visit in the Guidiguis subdivision, involving the recording and transcription of naturally occurring speech. Each sentence was analyzed using Cartographic Syntax (Rizzi, 1997; Cinque & Rizzi, 2010), focusing on the hierarchical organisation of the left periphery, including Spec-TopicP, Spec-FocP, and FinP. It was found that Tupuri systematically uses Spec-TopicP to encode topicalised constituents, with subjects and objects frequently accompanied by resumptive pronouns to preserve argument structure and coreference. Adjuncts, such as temporal, locative, and manner phrases, can also be fronted without resumptive elements. In all cases, topicalisation establishes a clear topic–comment structure, confirming that movement to the left periphery is a productive strategy for marking discourse relevance.